1990
DOI: 10.1161/01.cir.82.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal actions of neutral endopeptidase inhibition in experimental congestive heart failure.

Abstract: The present studies were designed to determine the action of neutral endopeptidase inhibition (NEP-I), an inhibitor of the degradation of atrial natriuretic factor (ANF), in congestive heart failure (CHF). Studies were conducted in two groups of anesthetized dogs with CHF induced by 8 days of rapid right ventricular pacing. Group 1 (n=5) received a specific NEP-I (SQ 28,603) at two doses administered sequentially-30 mg/kg followed by a 60 mg/kg i.v. bolus. Group 2 (n=5) received intravenous infusion of exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 25 publications
6
32
1
1
Order By: Relevance
“…Such a modulatory role of high circulating ANF levels in heart failure is suggested by a number of studies, using different experimental approaches such as autoimmune animals (17), monoclonal antibodies (18), exogenous ANF infusion (19), and inhibition of ANF metabolism (20).…”
Section: Introductionmentioning
confidence: 99%
“…Such a modulatory role of high circulating ANF levels in heart failure is suggested by a number of studies, using different experimental approaches such as autoimmune animals (17), monoclonal antibodies (18), exogenous ANF infusion (19), and inhibition of ANF metabolism (20).…”
Section: Introductionmentioning
confidence: 99%
“…tissue uptake, and protease degradation. NEP In previous studies, the renal response to NEPI, in dogs ently been shown to be present within the lung with and without chronic CHF, was characterized by a signifingly, pathophysiologic conditions that cause elecant diuresis and natriuresis without increases in GFR or RBF sma ANF also produce elevated levels of NEP (22,23 (46). One must however be cautious in interpreting this increase in urinary ANF despite the increases in both urinary cGMP and sodium, as this assay technique may detect open-ringed peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were conducted in two groups of anesthetized dogs (n = 6 pergroup) weighing 19-24 kg, with experimental acute CHF induced by rapid right ventricular pacing. This model is characterized by alterations in cardiorenal function and circulating hormones as observed in humans with acute biventricular heart failure (4,23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some reports, effects of NEP inhibition were in parallel with the elevation of plasma ANP level, 12,15 while in other reports, NEP inhibitors exerted effects without any change in the plasma ANP level 30,31 or their effects did not parallel increases in plasma ANP. 32 In the present experiment, candoxatril was administered to the rats by dissolving it in drinking water. This method might have caused the difference in the relationship among plasma ANP level, kidney NEP binding and cardiovascular actions, because in most studies, NEP inhibitors were administered using a bolus method.…”
Section: Discussionmentioning
confidence: 99%